Perceptions and Attitudes of Social Workers on Immigrants and Refugees: An Example of a Foundation University - Halim Baş; Serkan Eti (Sosyal Siyaset Konferansları Dergisi)
The phenomenon of migration is a driving force that encourages countries to produce public policies in terms of causes and consequences. At the same time, it can be an important trump or handicap in the light of different balances and radicalization in policy regimes in the world. However, although these strategies seem to have advantages in favor of countries, they open the door to a multidimensional social exclusion process for those who have to move from their country of origin or nationality. In this case, immigrants have to face various political, economic, and social arguments due to their status. Social work discipline, on the other hand, plays an intermediary role in the access of migrant groups, who are excluded from their economic, political, and social dimensions, to certain services in their country, while social workers perform important psychosocial tasks. The aim of this study is to reveal whether the attitudes asylum seekers in the framework of their professional understanding of the students who receive social work education as future social workers make a meaningful difference. According to the findings obtained in the study, it can be said that social service students have a very positive attitude towards asylum seekers and are on their side in defending their rights. Briefly, as a requirement of their profession, students are intensely supportive to ensure the rights of asylum seekers. As a result of bilateral comparisons, it is seen that undergraduate students are more accepting at the point of producing non-radical solution strategies than undergraduate students. In addition, it is seen that the gender of the students is not effective in their attitudes towards asylum seekers.